Uncertainties within South Africa’s goal of universal access to electricity by 2012 - Bekker, B.; Gaunt, C.T.; Eberhard, A.; Marquard, A. (Journal of Energy in Southern Africa, 2008)
The South African President in 2004 stated the pol-icy goal of universal access to electricity by 2012. This goal requires a significant adjustment of annu-al connection targets and electrification budgets, based on accurate knowledge of the number of electrified and non-electrified households in South Africa. Published data on the state of electrification, however, varies widely, with reported proportions of households electrified in 2005 varying from 57% to 80%. In addition, apparent discrepancies of tens of thousands of connections exist between annual new connection rates reported in different official publi-cations. Different definitions of Universal Access fur-ther impact strategic planning. This paper explores these uncertainties in relation to South Africa’s goal of Universal Access by 2012 by focusing on the availability and accuracy of South African electrifi-cation data, and the definitions, targets and electrifi-cation budgets associated with Universal Access.